2016
DOI: 10.1126/scisignal.aaf9109
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of TNAP compensates for reduced adenosine production and promotes ectopic calcification in the genetic disease ACDC

Abstract: ACDC (arterial calcification due to deficiency of CD73) is an autosomal recessive disease resulting from loss-of-function mutations in NT5E, which encodes CD73, a 5′-ectonucleotidase that converts extracellular adenosine monophosphate to adenosine. ACDC patients display progressive calcification of lower extremity arteries, causing limb ischemia. Tissue-nonspecific alkaline phosphatase (TNAP), which converts pyrophosphate (PPi) to inorganic phosphate (Pi), and extracellular purine metabolism play important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 52 publications
1
58
0
1
Order By: Relevance
“…Patients with mutations in CD73 gene exhibited ectopic calcification within the cardiovascular system that was dependent on the lack of TNAP-inhibiting adenosine. [65] These reports suggest that inhibitors of TNAP, such as adenosine, could be considered as potential preventive strategies in CAVD and supporting this hypothesis, we observed decreased serum and aortic root ALP activity in ApoE−/−LDLR−/− mice treated with adenosine deaminase inhibitor.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Patients with mutations in CD73 gene exhibited ectopic calcification within the cardiovascular system that was dependent on the lack of TNAP-inhibiting adenosine. [65] These reports suggest that inhibitors of TNAP, such as adenosine, could be considered as potential preventive strategies in CAVD and supporting this hypothesis, we observed decreased serum and aortic root ALP activity in ApoE−/−LDLR−/− mice treated with adenosine deaminase inhibitor.…”
Section: Discussionsupporting
confidence: 87%
“…[66] On the contrary, treatment with A2bR agonist significantly reduced the calcification volume of progenitor cell-derived teratomas from patients with CD73 deficiency. [65] Also in our recent work, we have shown that CD73−/− mice spontaneously developed aortic valve dysfunction increasing peak aortic flow and valvular Fig. 6 Adenosine receptors are widely express in human non-stenotic and stenotic aortic valves.…”
Section: Discussionmentioning
confidence: 92%
“…However, treatment with adenosine with or without the latter inhibitors enhanced the biomineralization of VICs, indicating that CD73 plays a central role in regulating pericellular adenosine levels, thus acting as a gatekeeper. Adenosine is known to down-regulate the neutral ALP (tissuenonspecific ALP, TNAP), and thereby reduces the calcification process by inhibiting the degradation of PP i to P i in vasculature and myocardium (43). For the latter tissue types, a consequent reduction of extracellular adenosine levels enhances TNAP activity, which promotes the calcification process (17,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is known to down-regulate the neutral ALP (tissuenonspecific ALP, TNAP), and thereby reduces the calcification process by inhibiting the degradation of PP i to P i in vasculature and myocardium (43). For the latter tissue types, a consequent reduction of extracellular adenosine levels enhances TNAP activity, which promotes the calcification process (17,43,44). In our model, the degeneration of VICs is induced by an experimental increase in the availability of P i , so that the inhibiting effect of TNAP can be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…(54) We also demonstrated that immunofluorescence signal for 16 both proteins, alkaline phosphatase and eNPP1 was abundant in stenotic aortic valves, 17 with significant accumulation of alkaline phosphatase within the calcification areas.18 Patients with mutations in e5NT gene exhibited ectopic calcification within the 19 cardiovascular system. (55) These reports suggest that inhibitors of TNAP, like 20 adenosine, could be considered as potential preventive strategies in CAVD (56). 21 However, these beneficial adenosine effects could be also dependent on the type of 22 activated adenosine receptors and the activity of endothelial or immune cell-surface 23 ecto-adenosine deaminase.…”
mentioning
confidence: 99%